A influência do uso das tecnologias informatizadas no comportamento docente - Maria de Fatima Uchoa de Castro Macedo (2000)
Analyses the influence of the use of computers in the behavior of university professors toward the importance of information in the contemporary society, and toward the potential of the use of computers in the educational procedures. The theoretical references includes the analysis of some works in the area of social, organizational, and university professor behavior in order to identify the tendencies of computers technology in education. The research took place at Centro de Ciencias da Educacao (CEE), Universidade Federal do Piaui (UFPI), Campus Ininga, Teresina-Piaui/Brazil, through the first semester of the year 2000. The subjects of the present work were 33 full professor from the Pedagogy Department staff. The data collection was achieved through questionnaires and interviews, in two point moments \ January and July, 2000 \ in order to verify if there was any change in the group concerning the use of the computers after the insertion of computers in the Department. The subjects were labeled as three groups: GROUP A (advanced users), GROUP B (beginner users), GROUP C (not users). This is a case study, to which we recurred to a quantitative approach, emphasizing sometimes detached aspects, sometimes quantifiable data. Based in the results, the conclusions, among others are: a) The behavior of the subjects is characterized primarily for the use of conventional sources of information; b)However, they manifested to be open to technological innovations, even before the insertion of the computers in the work environment; c) the most common ways of computer uses attends to the inception of technology as an auxiliary tool for education, through typewriting, followed for the search of information in the Internet; in a lower scale, the organization of pedagogic materials, and the production of scientific papers; c) most of the subjects (87,88%), do not make activities with the students, through Internet, for lack of skills on how to use this technology. The other subjects make use of it suggesting sites that might be interesting for the students, according to the contents of the discipline they are teaching. Such results allowed to identify the evolution of the group regarding the use of computers, for the growing interest for the Internet detected in the second interviews and questionnaires. We verified, also, that it is not enough to provide technology without providing an informational culture, without a planned, systematic and conscious practice, lastly, without a policy that contemplates the utilization of technology potential.